The Relationship Between Tiktok Exposure and English Vocabulary Acquisition Among English Education Students at Tadulako University - Gusti Ayu Kadek Velli Amanda; Konder Manurung; Moh. Abraham Akbar Eisenring; Afrillia Anggreni (Universitas Islam Negeri Palopo, 2026)
This study aimed to investigate the relationship between TikTok exposure and English vocabulary acquisition among English Education students at Tadulako University. Using a quantitative correlational design, data were collected from 60 students selected through purposive sampling using an online questionnaire and analyzed using SPSS. The findings showed a mean score of 43.4 for TikTok exposure and 36.9 for vocabulary acquisition. Spearman’s Rank Correlation revealed a correlation coefficient of 0.494 with a significance value of less than 0.001, indicating a positive and statistically significant relationship between TikTok exposure and English vocabulary acquisition. These findings suggest that students with higher TikTok exposure tend to have higher levels of English vocabulary acquisition.